2015
DOI: 10.3892/mmr.2015.4200
|View full text |Cite
|
Sign up to set email alerts
|

K604, a specific acyl-CoA:cholesterol acyltransferase 1 inhibitor, suppresses proliferation of U251-MG glioblastoma cells

Abstract: Glioblastoma is the most aggressive type of brain tumor and has a poor prognosis. Increased levels of cholesteryl ester and simultaneous expression of acyl‑CoA:cholesterol acyltransferase 1 (ACAT1) in tumor cells indicated that cholesterol esterification is critical to tumor growth. The present study confirmed that human glioblastoma tissues as well as the glioblastoma cell line U251‑MG showed significant expression of ACAT1. ACAT1 expression in U251‑MG cells increased in a cell proliferation‑dependent manner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…ACAT1 encodes a mitochondrially localized acetyl-CoA acetyltransferase. Inhibition of ACAT1 by Avasimibe inhibited cell growth by inducing cell cycle arrest and apoptosis in glioblastoma cell lines [ 6 , 55 ]. Further, inhibition of ACAT1 has also been shown to suppress growth and metastasis of pancreatic cancer [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…ACAT1 encodes a mitochondrially localized acetyl-CoA acetyltransferase. Inhibition of ACAT1 by Avasimibe inhibited cell growth by inducing cell cycle arrest and apoptosis in glioblastoma cell lines [ 6 , 55 ]. Further, inhibition of ACAT1 has also been shown to suppress growth and metastasis of pancreatic cancer [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Would inhibiting ACAT1 SOAT1 affect the progression of other human diseases? Recent results in mouse models show that ACAT1 SOAT1 is also a potential target for treating various forms of cancer (227)(228)(229). In addition, in a mouse model for atherosclerosis, a recent study showed that, in contrast to the result of knocking out ACAT1 SOAT1 in the whole body, knocking out ACAT1 SOAT1 in the myeloid cell lineage (including monocytes/macrophages, neutrophils, and eosinophils) actually reduces atherosclerotic lesions (230).…”
Section: Acat1 Soat1 Inhibitorsmentioning
confidence: 99%
“…This enzyme is highly expressed in glioblastomas and in cancer of the prostate or pancreas; its expression level correlates inversely with patient survival [ 28 , 29 , 230 235 ]. Genetically silencing SOAT1/ACAT1 or blocking its activity using the inhibitors K604, ATR-101 or avasimibe effectively suppresses tumor growth in several cancer xenograft models [ 28 , 230 232 ]. These results suggest that targeting SOAT1 and cholesteryl ester synthesis may be a promising anti-cancer strategy.…”
Section: Introductionmentioning
confidence: 99%